2014
DOI: 10.1186/1757-2215-7-44
|View full text |Cite
|
Sign up to set email alerts
|

Tribbles expression in cumulus cells is related to oocyte maturation and fatty acid metabolism

Abstract: BackgroundIn mammals, the Tribbles family includes widely expressed serine-threonine kinase-like proteins (TRIB1, TRIB2 and TRIB3) that are involved in multiple biological processes including cell proliferation and fatty acid (FA) metabolism. Our recent studies highlighted the importance of FA metabolism in cumulus cells (CC) during oocyte maturation in vertebrates and reported a higher TRIB1 expression in CC surrounding in vivo mature oocytes as compared to immature ooocytes in mice and cows. The objective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…We hypothesize that in the COC, FAO may undergo an initial increase in activity as a response to etomoxir, increasing transcription of essential FAO genes, and briefly metabolizing lipids before inhibition. This hypothesis is supported by recent reports in mouse COC where expression of genes involved in FAO were altered after FAO inhibition (Brisard et al 2014). Abundance of genes involved in FAO is also increased in COC after treatment with rosiglitazone, an agent known to inhibit FAO (Dunning et al 2014).…”
Section: Discussionsupporting
confidence: 78%
“…We hypothesize that in the COC, FAO may undergo an initial increase in activity as a response to etomoxir, increasing transcription of essential FAO genes, and briefly metabolizing lipids before inhibition. This hypothesis is supported by recent reports in mouse COC where expression of genes involved in FAO were altered after FAO inhibition (Brisard et al 2014). Abundance of genes involved in FAO is also increased in COC after treatment with rosiglitazone, an agent known to inhibit FAO (Dunning et al 2014).…”
Section: Discussionsupporting
confidence: 78%
“…Currently, three mammalian homologs of the tribbles gene are known. One of these, TRIB3, plays an important role in multiple signaling pathways, coordinating crucial cellular processes such as apoptosis, glucose and lipid metabolism, adipocyte differentiation, and cell stress (15,(24)(25)(26)(27). TRIB3 is overexpressed in many cancers, but whether TRIB3 is upregulated in GC has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Dunning et al () plus data herein showed that a major portion of FAO in the mouse cumulus‐oocyte complex derives from the cumulus cells. Expression of Cpt1b mRNA in the cumulus cells increases during meiotic maturation and Trib1 and Trib3 (Ser‐Thr kinases involved in FAO regulation) mRNA abundance increased in mouse cumulus cells during in vitro maturation, whereas Acaca transcript levels decreased under these conditions (Brisard et al, ). High FAO activity in cumulus cells suggests that these somatic cells are an important source of fatty acid‐derived energy during oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%